The effect of curing temperature on cellulose nanocrystal reinforced natural rubber latex - N. A. H., Jailudin; Khairatun Najwa, Mohd Amin (Universiti Malaysia Pahang, 2020)
Cellulose nanocrystal (CNC) was extracted from filter paper and isolated via sulphuric acid hydrolysis. This CNC was used as reinforcing elements in natural rubber latex (NRL) along with the cross-linking agents to prepare nanocomposite films. The effect of CNC loading on the mechanical properties, functional group presence and the glass transition temperature (Tg) of CNC/NRL nanocomposite at curing temperature of 70°C and 80°C were studied, respectively. CNC size and dimension was characterized using transmission electron microscope (TEM). Significant improvement of Young’s modulus was observed as a result of the addition of CNC loading at 3 wt.% and the Tg only showed a small increase upon the addition of CNC. The best nanocomposite was found at a curing temperature of 80°C with a tensile strength of 144% improvement.